2017
DOI: 10.3389/fmicb.2017.00990
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Value Chemoattractants Are Preferentially Recognized at Broad Ligand Range Chemoreceptor of Pseudomonas putida KT2440

Abstract: Bacteria have evolved a wide range of chemoreceptors with different ligand specificities. Typically, chemoreceptors bind ligands with elevated specificity and ligands serve as growth substrates. However, there is a chemoreceptor family that has a broad ligand specificity including many compounds that are not of metabolic value. To advance the understanding of this family, we have used the PcaY_PP (PP2643) chemoreceptor of Pseudomonas putida KT2440 as a model. Using Isothermal Titration Calorimetry we showed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 66 publications
5
30
1
Order By: Relevance
“…The individual LBD of Tar exists in a dynamic equilibrium between monomers and dimers and ligand binding induces dimerization since the ligand interacts with both monomers to stabilize the dimer (Milligan and Koshland, ; Yeh et al , ; Biemann and Koshland, ; Yeh et al , ). Similar to Tar, some other helical LBDs also alter the oligomeric state upon ligand binding, such as 4HB domains of PcaY_PP (Fernandez et al , ) and CtpH (Rico‐Jimenez et al , ), HBM domains of McpS (Lacal et al , ) and McpQ (Martin‐Mora et al , ), and PilJ domain of McpN (Martin‐Mora et al , ). On the contrary, the oligomerization of some dCACHE and sCACHE LBDs is not altered by ligand binding and their ligand binding sites are not located at the dimeric interface (Rico‐Jimenez et al , ; Martin‐Mora et al , ; Gavira et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The individual LBD of Tar exists in a dynamic equilibrium between monomers and dimers and ligand binding induces dimerization since the ligand interacts with both monomers to stabilize the dimer (Milligan and Koshland, ; Yeh et al , ; Biemann and Koshland, ; Yeh et al , ). Similar to Tar, some other helical LBDs also alter the oligomeric state upon ligand binding, such as 4HB domains of PcaY_PP (Fernandez et al , ) and CtpH (Rico‐Jimenez et al , ), HBM domains of McpS (Lacal et al , ) and McpQ (Martin‐Mora et al , ), and PilJ domain of McpN (Martin‐Mora et al , ). On the contrary, the oligomerization of some dCACHE and sCACHE LBDs is not altered by ligand binding and their ligand binding sites are not located at the dimeric interface (Rico‐Jimenez et al , ; Martin‐Mora et al , ; Gavira et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…These experiments have resulted in two different scenarios. On one hand, individual 4HB or HBM domains are primarily monomeric in its ligand-free state and ligand binding induces dimerization 25 , 32 , 42 , 43 . In contrast, dCACHE domains were found to be monomeric in the absence and presence of ligands 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have shown that the affinity of ligands for the LBD correlate with the magnitude of the chemosensory output 16 , 43 . However, this correlation was not observed for the PA2652 ligands (Figs 3 and 5 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, when the PR of a Pseudomonas aeruginosa chemoreceptor was fused to the signaling domain of the Tar chemoreceptor to create a chimera in E. coli, correlations were found between ligand affinity and signal output or attractant utilization using a fluorescence resonance energy transfer (FRET) assay (41). However, this pattern does not hold for all systems, such as the Pseudomonas putida chemoreceptors for TCA intermediates (McpS) and cyclic carboxylates (PcaY_PP) that do not show a distinct difference in ligand-binding affinity for differently utilized attractants (42,43). In conclusion, small Combining DSF with Biolog PM plates is an effective and facile method for screening the ligand profile of a chemoreceptor (30,33).…”
Section: Discussionmentioning
confidence: 99%